(untitled) (Global Journal of Human-Social Science, 2023)
Rereading Little Women by Lousia May Alcott an enduring classic in American literary history the present paper argues that Mrs March as a moderate feminist drawing much from the transcendental thoughts about individualism parents her daughters with empathy and care while acknowledging the limitations of gender roles in the mid-19th century New England context The March girls undergo journeys of growth coping with negative emotions related to class and gender and developing individual personalities under their mother s guidance Mrs March s empathic parenting leaves a lasting impact on her daughters empowering them to navigate the complexities of their world and embrace their true selves with strength compassion and love